2006
DOI: 10.1007/s11099-006-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the photosynthetic capacity of cones on a larch (Larix kaempferi) canopy

Abstract: The seasonal changes of photosynthesis of cones of Japanese larch (Larix kaempferi Carr.) trees showed that gross photosynthetic rate of young cones (P G) was 2–3 µmol m−2 s−1 at surface area unit and P G/R D (dark respiration of cones) peaked about 0.7 in the same period, indicating that 70 % of respiratory CO2 was re-fixed. With maturation, P G and P G/R D sharply decreased. Chlorophyll content in cones was 3–20 % of that in leaves, which made it a limiting factor for photosynthesis and its content was close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Nothing is known of the photosynthetic capacity of microphylls and megaphylls in cycad strobili, yet most are green during early stages of development. In gymnosperms, female strobilus photosynthesis is often critical to strobilus formation, contributing a significant proportion of an individual’s respiratory costs, while male strobili seem to rely largely on foliar photosynthates for growth and development ( McDowell et al 2000 ; Matyssek and Benecke 2005 ; Wang et al , 2006a , 2006b ). If these structures in cycads contribute to overall carbon gain, this may explain the lack of difference found in photosynthetic and respiration rates between male and female leaves in some species.…”
Section: Discussionmentioning
confidence: 99%
“…Nothing is known of the photosynthetic capacity of microphylls and megaphylls in cycad strobili, yet most are green during early stages of development. In gymnosperms, female strobilus photosynthesis is often critical to strobilus formation, contributing a significant proportion of an individual’s respiratory costs, while male strobili seem to rely largely on foliar photosynthates for growth and development ( McDowell et al 2000 ; Matyssek and Benecke 2005 ; Wang et al , 2006a , 2006b ). If these structures in cycads contribute to overall carbon gain, this may explain the lack of difference found in photosynthetic and respiration rates between male and female leaves in some species.…”
Section: Discussionmentioning
confidence: 99%
“…The same physiological argument can be put forward, whereby resources in denser crowns have to be allocated to the maintenance of non-reproductive shoots. Conversely, self-shading and light occlusion over the maturing cones, as they are located below two vegetative shoots, can result in losses in the photosynthetic activity of the cones in very dense crowns [55]. This would result in a reduction on the available photosynthates for cone development and enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Larix olgensis has been identified as a major fast-growing and high-yielding tree species in northeastern China [59]. Research on the photosynthetic characteristics of larch has been reported [60][61][62][63][64][65][66][67], but only a few studies have examined the photosynthetic characteristics of Larix olgensis [65][66][67]. Most previous studies have focused on diurnal changes or the response of photosynthetic characteristics to different concentrations of nitrogen or phosphorus rather than their spatial and seasonal variations.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [65] analyzed spatial differences in crown photosynthesis in Larix olgensis but did not explain the reason for these spatial differences. Wang et al [62] proved that the seasonal changes in the photosynthetic capacity of Larix kaempferi Sarg. depend on chlorophyll content.…”
Section: Introductionmentioning
confidence: 99%